THE RELATIONSHIP BETWEEN KNOWLEDGE, ATTITUDE, AND BEHAVIOR OF BREASTFEEDING AND INTAKE OF COMPLEMENTARY FEEDING WITH NUTRITIONAL STATUS OF CHILDREN AGED 6-24 MONTHS AT KESUNEAN HEALTH CENTER CIREBON - Mauli Ardhiya; Ignatius Hapsoro; Shofa Nur Fauzah (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: The insufficient nutrient intake in the certain time may affect physical growth and development of children. The percentage of babies with exclusive breast feeding are only 37.3%. It is still under the national target. This research aims to examine the correlation of knowledge, attitude, and behavior of breastfeeding and intake of complementary feeding with nutritional status of children. Methodology: This study was a cross sectional research conducted in Kesunean Health Center, Cirebon City. Totally 100 mothers of children aged 6 to 24 months was selected by consecutive sampling. The nutritional status was calculated based on weight of age whereas the predictors (knowledge, attitude, behavior) was asked by 31 questions. The statistical analysis used Spearman test. Results: The results of this study found that knowledge (p=0.001 and r=0.561), attitude (p=0.001 and r=0.498), and behavior (p=0.001 and r=0.606) had a correlation with nutritional status in Kesunean Health Center. Conclusion: Knowledge, attitude, and behavior of mother had correlation with nutritional status. Public health center should promote the importance of breast milk and provide the counseling to the mother. Keywords: breastfeeding, intake of complementary feeding, nutritional status of children